Penerapan Penganggaran Pada Organisasi Sektor Publik Ikatan Pemuda Mahasiswa Koto Majidin-Jambi (IPMKM-J) - Sahrani Amalia; Ratih Kusumastuti (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to find out how the Koto Majidin-Jambi Student Youth Association (IPMKM-J) implements a budgeting system on every incoming and outgoing fund that they will use in implementing the IPMKM-J work program. The method used in this study is qualitative method, which is a method that collects data which is then explained in words. Primary data were obtained from observations and interviews conducted with parties involved in IPMKM-J and secondary data were obtained from literature studies such as scientific journals, books, and e-books. The result of his research is that IPMKM-J has implemented a budgeting system in preparing budgets for the work programs they hold. The budgeting they made was the Draft Cost Budget (RAB).